CUSTOS E OTIMIZAÇÃO DE ROTAS NO TRANSPORTE DE LEITE A LATÃO E A GRANEL: UM ESTUDO DE CASO - da Silva, Irauê Casarin Vieira (2011)
This present work compares the can and the bulk milk transportation systems in the first run, taking into consideration the economical cost indexes, leveling point, optimization of routes and the forms of payment for the freight.The study was carried out at a milk receptor company in the western side of Minas Gerais and the optimization model was based on the Vehicles Path Vertices Problem ( PPV ). The SisGRAFO software was used. In the analysis operational deficiencies in the bulk milk transportation system were verified, as well as deficiencies in the remuneration of the carters and in the optimization of routes. The adoption of a system which rewards the carter per transported volume instead of traveled distance comes as a suggestion.